Effect of Seeds Soaking in Solutions of Some Calcium Salts on Saline Stress Tolerance of Barley Plant - AL- Rahmaini, H. F.; AL Hadithi, T. R.; Atia, F. E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Seeds of barley ( Hordeum vulgare L.) plant var. California Marriout were soaked in solutions of calcium sulphate and calcium chloride at different concentrations (0.5%,1.0%,5.0%) for different periods of time(3,6,12) h with continuous aeration . Seeds were planted in petridishs. Seedling of some treatment were transferred to the solution culture. The nutrient solution used was that of Arnon and Hoagland but at 1:10 strength. Different concentrations of NaCl were used in the nutrient solution (100,150, 200) m M . Unsoaked seeds and soaked in distilled water were used for comparison . Salt stress tolerance was evaluated by different morphological parameters. Results showed that the adverse effect of saline stress were reduced by soaking the seed in distilled water and to higher extent by soaking them in solutions of calcium suiphate or   calucium chloride at 1% concentration for 6h . The reduction in the adverse effects of saline stress was higher in the caseof soaking the seeds in calcium chloride . Result also showed acute  reduction in the adverse effects of saline stress in plant grown at 100mm NaCl.   Results supported the role of calcium as a second messenger in plant cells under saline stress